Determinasi Terhadap Kinerja Perusahaan - Aang Syahdina; Michael Chan; Rivaldi Ferdian Lesmana; Yohanes Suryadi Sinaga; Eca Oktavia; Ferris Aryadafa (JIBEMA: Jurnal Ilmu Bisnis, Ekonomi, Manajemen, dan Akuntansi, 2026)
This study aims to analyze and obtain empirical evidence regarding the effect of green accounting, profitability, and leverage on the financial performance of mining companies. The population of this study consists of 64 companies, and purposive sampling was applied, resulting in 10 companies selected as the research sample. The sample data were then analyzed using EViews 13. The results show that, partially, profitability and green accounting have no significant effect on financial performance, while leverage has a significant effect on financial performance. Based on these findings, it can be concluded that simultaneously, green accounting, profitability, and leverage contribute to the financial performance of mining companies. These results indicate that mining companies need to pay attention not only to financial aspects but also to the implementation of environmental accounting as part of corporate responsibility. Although green accounting and profitability do not have a partial effect, their implementation together with leverage can improve overall company performance.